PEMIKIRAN MUHAMMAD SHAHRUR TENTANG RELASI FILSAFAT BAHASA DAN MODERNITAS - Esha, Muhammad Inâ€™am (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
Study on philosophy of language, especially on contemporary Islamic thinker, is very needed for enriching thinking spectrum on this object. We hope this paper can open our horizon on this topics and enhance our knowledge especially on philosophy of language in Islamic perspective. This paper affords to describe Shahrurâ€™s thought on relation between philosophy of language and modernity.Â  Important findings of the paper are: first, language as important reality in human life. With language realities of human life can be articulated well. So, language is a mirror of reality. Second, when we understand that â€œlanguage as mirror of realityâ€, actually we make language passively. Shahrurâ€™s philosophical thought on language gives us understanding that language can be functioned as active tool for developing progressive ethos and value for supporting modernity in Islamic world. Third, Philosophy of language gives us possibility for raising a new horizon of understanding on language as object of study.Keywords: Shahrur, Filsafat Bahasa, Modernitas